An acetylcholinesterase inhibition biosensor based on a reduced graphene oxide/silver nanocluster/chitosan nanocomposite for detection of organophosphorus pesticides. Issue 15 (7th August 2015) - Zhang, Yanli; Liu, Hongjun; Yang, Zhongming; Ji, Shunlin; Wang, Junfang; Pang, Pengfei; Feng, Lili; Wang, Hongbin; Wu, Zhan; Yang, Wenrong
<x xml:space="preserve">Abstract</x> A sensitive electrochemical acetylcholinesterase biosensor based on a reduced graphene oxide and silver nanocluster modified glassy carbon electrode was developed.